Makerspace in Education - Disruptive Technology or Just Another Passing Fad? - Jane Gilbert (New Zealand Journal of Teachers' Work)
Makerspaces are now common in schools. This idea, which originated outside education, is being advocated as a way to improve student engagement in learning and/or to foster creativity and/or innovation. It is also linked with “future-focused” education and is seen by some as a potentially disruptive force for good in education. This paper evaluates these claims. It looks at the origins of the makerspace concept and at how and why it was taken up by educationists. Via an exploration of the ideas about knowledge, learning and education assumed by its proponents, it assesses makerspace’s general educative potential and its likely contribution to the development of future-focused education. It concludes that the makerspace idea could be usefully disruptive in terms of education’s future development, but that this is unlikely without system-wide cognitive change.